Finite-difference methods for poisson equations - Dai, Weiyuan (Nanyang Technological University, 2022)
Poisson equation is a very important partial differential equation in physics and engineering applications. According to the principle of the finite difference method, the simulation region is divided into a series of discrete nodes with equal spacing grid. Then Poisson equation can be transformed into multiple linear equations, which can be solved in MATLAB program quickly and accurately.